2005
DOI: 10.1074/jbc.m406613200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for Vascular Endothelial Growth Factor as an Autocrine Survival Factor for Embryonic Stem Cells during Hypoxia

Abstract: Vascular endothelial growth factor (VEGF) is best known for its angiogenic activity on endothelial cells, but it also affects neurons, pneumocytes, and other mature cell types as well as endothelial, neural, and hematopoietic progenitors. Here, we examined its effect on pluripotential embryonic stem (ES) cells under hypoxic stress. ES cells were found to produce VEGF and to express VEGF receptor-2 and neuropilin-1 (Nrp-1), a VEGF 165 isoform-specific receptor. During hypoxia, expression levels of VEGF, Flk-1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 68 publications
2
74
1
Order By: Relevance
“…However, our observation of VEGF-A and Flk1 mRNA expression in undifferentiated ES cells suggests even earlier embryonic effects, in which VEGF-A signaling is part of the mechanism (in addition to TGF␤ signaling) (Tropepe et al, 2001) that suppresses p-NSC formation and survival in vitro before neural plate formation of Nestin ϩ cells is first detected at E7.5. Although undifferentiated ES cells in hypoxic conditions respond to VEGF-A as a survival factor (Brusselmans et al, 2005), this finding is different from the present results. The previous effects were seen only under hypoxic conditions and only on undifferentiated ES cells, whereas the present results were specific to primitive neural stem cells under nonhypoxic conditions.…”
Section: Discussioncontrasting
confidence: 57%
“…However, our observation of VEGF-A and Flk1 mRNA expression in undifferentiated ES cells suggests even earlier embryonic effects, in which VEGF-A signaling is part of the mechanism (in addition to TGF␤ signaling) (Tropepe et al, 2001) that suppresses p-NSC formation and survival in vitro before neural plate formation of Nestin ϩ cells is first detected at E7.5. Although undifferentiated ES cells in hypoxic conditions respond to VEGF-A as a survival factor (Brusselmans et al, 2005), this finding is different from the present results. The previous effects were seen only under hypoxic conditions and only on undifferentiated ES cells, whereas the present results were specific to primitive neural stem cells under nonhypoxic conditions.…”
Section: Discussioncontrasting
confidence: 57%
“…Previously, Carmeliet et al (25) suggested that hypoxia reduces stem cell proliferation and increases apoptosis through HIF-1␣. Accordantly, a recent report (26) suggested that ESC apoptosis is found to be dependent on the cel- lular differentiation and on the duration and degree of hypoxia. In this context, it is interesting to note that low O 2 tension inhibits differentiation of hESCs (27) and human marrow stromal cells (28).…”
Section: Discussionsupporting
confidence: 52%
“…31 In addition to its function as an essential coreceptor in neuronal guidance and angiogenesis, [23][24][25][26][27][28] NRP-1 has also been implicated as a novel mediator of the primary immune response. 32,33 Moreover, the expression of NRP-1 can be stimulated in response to tissue injury or hypoxic conditions, 34,35 and it is highly expressed in diverse solid tumors, such as prostate, breast, pancreatic, lung, ovarian, and gastrointestinal carcinomas. 10,28,36,37 Increased expression of NRP-1 has been correlated with tumor growth and vascularization in vivo and with invasiveness in human cancer.…”
Section: Discussionmentioning
confidence: 99%